Assessment policies and academic performance within a single course: the role of motivation and self-regulation. Issue 8 (17th November 2019) - Kickert, Rob; Meeuwisse, Marieke; M. Stegers-Jager, Karen; V. Koppenol-Gonzalez, Gabriela; R. Arends, Lidia; Prinzie, Peter
Abstract: Despite the frequently reported association of characteristics of assessment policies with academic performance, the mechanisms through which these policies affect performance are largely unknown. Therefore, the current research investigated performance, motivation and self-regulation for two groups of students following the same statistics course, but under two assessment policies: education and child studies (ECS) students studied under an assessment policy with relatively higher stakes, a higher performance standard and a lower resit standard, compared with Psychology students. Results show similar initial performance, but more use of resits and higher final performance (post-resit) under the ECS policy compared with the psychology policy. In terms of motivation and self-regulation, under the ECS policy significantly higher minimum grade goals, performance self-efficacy, task value, time and study environment management, and test anxiety were observed, but there were no significant differences in aimed grade goals, academic self-efficacy and effort regulation. The relations of motivational and self-regulatory factors with academic performance were similar between both assessment policies. Thus, educators should be keenly aware of how characteristics of assessment policies are related to students' motivation, self-regulation and academic performance.